Analysis of Students' Difficulties in Mastering English Vocabulary at Elementary School Students - Ryan, Tenku; Islam, Muhammad Hifdil; Ferdiyanto, Feri (International Journal of English Education and Linguistics (IJoEEL), 2024)
The purpose of this study was to describe the students difficulties in vocabulary mastery and the factors that caused their difficulties in mastering vocabulary. This research employed a qualitative approach using a phenomenology design. The data were gathered by observation, interview, and document review. Data technique and data source triangulation were used to validate the collated data. The result of this research revealed that several students had difficulties with vocabulary mastery. This study showed that, first, the difficulties encountered by students were that they had difficulties translating words or sentences in English into Indonesian and vice versa. Students also experienced difficulties in understanding the meaning of words, pronunciation, misspelling, and remembering or memorizing English vocabulary. Secondly, there were some factors that caused students difficulties in vocabulary mastery. Students were reluctant to open dictionaries and less interested in learning English. This condition became a hindrance to their ability to practice English regularly. The other issues were external factors such as inadequate facilities and the negative influence of friends that, in the end, have made it difficult to learn English, especially, vocabulary mastery.